Agricultural Correlates of Linear Growth and Key Modifiers Among Children Under Two Years in Rural Uganda. - Gunaratna, Nilupa.; Duggan, Christopher (Christopher P.); Griffiths, Jeffrey K. (Tufts University. Tisch Library., 2016)
This paper-in-progress investigates possible links between agricultural investments or productivity and linear growth in young, rural, Ugandan children.; Nutrition School: Technical Reports.; Keywords: Technical Report, Agriculture, Linear Growth, Paper-in-progress.